Driver's side curtain air bag-related globe rupture. (4th June 2018) - Porter, Ashley J; Hayes, Rylan; Lee, Lawrence; O'Hagan, Stephen
Abstract : A 35-year-old man presented after a high-speed motor vehicle accident and the driver's side curtain air bag causing blunt force trauma rupturing his right globe. The tangential force of the air bag resulted in an unusual arcuate horseshoe-shaped rupture through the lateral rectus insertion, causing avulsion of the muscle and tearing the sclera, with the apices of the tear extending anteriorly towards the limbus. Repair of the globe rupture was undertaken, and secondary vitrectomy revealed that the scleral tear had not involved the retina abutting the ora serrata. Silicone oil tamponade was used to fill the globe and the postoperative best corrected vision was 6/9. This is the first reported case of a ruptured globe caused by a side curtain air bag, resulting in a uniquely shaped arcuate scleral wound combined with lateral rectus avulsion, not associated with rhegmatogenous retinal damage, and is the first air bag-related globe rupture with scleral involvement to report a final best-corrected visual acuity better than 6/60.